Is there equity of access to revascularisation in Wales by socioeconomic deprivation? - Evans, Lloyd (International Journal of Population Data Science, 2019)
Background Long-standing evidence of inequity has been shown to exist in the management of patients with heart disease. The majority of UK studies during the last 20 years have concluded that patients living in the most deprived areas were disadvantaged by lower revascularisation rates, despite having a higher level of need. Over the last 10 years, a systematic approach at tackling health inequity has played an important role in public health policy and practice throughout the UK. National service frameworks for cardiac disease have contributed to significant changes to the way coronary revascularisation is provided. Their aim is to provide access to the best possible treatment in timely fashion for all with heart disease. Aim To investigate the impact of service redesign in the provision of revascularisation procedures on the historical socioeconomic inequity in revascularisation rates for patients with heart disease. Methods A retrospective cohort design was created through the linkage of population administrative datasets, with cohorts created in both the pre- and post-service redesign periods. Cox Proportional Hazards models were used to estimate the likelihood of receiving revascularisation to see did these differ between periods by socioeconomic status. Results Revascularisation was provided equitably by socioeconomic deprivation after the service redesign, whereas pre-service redesign, subjects resident in the most deprived quintile were 20% less likely to receive revascularisation. Measures to improve access to services are working, with previous signs of socioeconomic inequity of access to revascularisation not apparent, but rather increased access for all and in a timelier manner regardless of socioeconomic deprivation. Conclusion While inequities and inequalities remain throughout healthcare today, this research provides evidence that measures can be successful in hard to reach groups such as those living in the most deprived areas, and these unnecessary variations can be reduced or eradicated in the future.